Emotions and risk attitudes - Armando N. Meier (Deutsches Institut für Wirtschaftsforschung (DIW), 2021)
Previous work has shown that preferences are not always stable across time, but surprisingly little is known about the reasons for this instability. I examine whether variation in people's emotions over time predicts changes in risk attitudes. Using a large panel data set, I identify happiness, anger, and fear as significant correlates of within-person changes in risk attitudes. Robustness checks indicate a limited role of alternative explanations. An event study around the death of a parent or child further confirms a large relationship between emotions and risk attitudes.
Keywords: D01; D90; D91; 330; Emotions; happiness; risk attitudes; risk preferences; preference stability; SOEP